Development and Psychometric Evaluation of the Military Cadets’ Mental Health Risk Scale (MCMHRS) in Chinese Military Academy Cadets - Feifei Wang; Jia Guo; Guoyu Yang (Healthcare, 2026)
Background: Military academy cadets face training, study, and adaptational pressures that elevate the risk for mental health problems and functional impairment. Existing tools are either generic symptom checklists or narrow resilience scales; none integrates environmental risk, individual vulnerability, and protective resources within a unified hierarchical model relevant to this population. Methods: We developed and psychometrically evaluated the Military Cadets’ Mental Health Risk Scale (MCMHRS). After item generation and two-round Delphi review (n = 15), a 64-item pool was administered to 610 Chinese cadets (mean age 19.45 ± 1.42 years; 82.6% male), randomly split into calibration (n = 244) and validation (n = 366) subsamples for exploratory and confirmatory factor analyses and reliability/validity testing against the PHQ-9, GAD-7, and WHO-5. Results: The final 53-item scale comprised 13 first-order factors nested within three second-order dimensions, with excellent fit (RMSEA = 0.043, CFI = 0.978), strong internal consistency (α = 0.968), and coherent correlations with PHQ-9 (r = 0.70), GAD-7 (r = 0.69), and WHO-5 (r = −0.58). Conclusions: The MCMHRS shows initial evidence of being a psychometrically sound, culturally relevant, multilevel assessment tool that may support early identification and tiered intervention in cadet mental healthcare pending further longitudinal validation.